Municipal solid waste collection optimization in Singapore - XUE, Weijian (Institutional Knowledge at Singapore Management University, 2015)
Along with the rapid urbanization and population growth during past decades, the social and environmental impacts caused by municipal solid waste (MSW) have been paid increasing attention. How to collect and dispose the booming amounts of MSW turned to be a hot topic. Due to its advantages of costefficiency and environmental concerns, the incineration is replacing the direct landfilling for dealing with the MSW worldwide. Under the consideration of the limited number of incineration plants and the complicated situation of transportation in both spatial and temporal dimensions around different cities, how to effectively and efficiently allocate the incineration resources for different areas in different cities turns to be a very meaningful topic, especially in the high population density areas (e.g. Singapore). In this research, the current MSW collection and disposal in Singapore is reviewed, especially the problematic allocation of incineration resources, and a spatial allocation model is also proposed, and successfully implemented within the context of Singapore. On the other hand, few limitations of this study are also discussed, some of which will also be the research directions in the future